Prevalence of Alcohol Consumption and Alcohol Use Disorder among Adolescents in Ibanda District, South Western Uganda: A Cross-Sectional Study - Nyemara, Novatus; Maling, Samuel; Rukundo, Aloysius; Rukundo, Godfrey Z.; Ashaba, Scholastic; Merkel, Richard; Okello, Elialilia S. (Open Journal of Social Sciences, 2023)
Background: Alcohol use disorder ranks as the most prevalent mental disorder globally. However, studies on alcohol use disorder among adolescents in rural areas in sub-Saharan Africa are scarce. Despite having public health consequences, alcohol use disorder remains one of the most undertreated mental disorders. This study determined the prevalence of alcohol use and alcohol use disorder and its associated demographics in an adolescent population from Southwestern Uganda. Understanding the prevalence of alcohol use and alcohol use disorder among adolescents is crucial in investing in early intervention strategies. Methods: A population-based cross-sectional study was conducted between October and December 2019 among a random sample of 308 adolescents residing in Ibanda District. The area of study was selected using-multi stage cluster sampling. Alcohol use disorder was defined to include possible hazardous use, harmful use, and dependent use of alcohol and was screened using the Alcohol use disorder Identification Test with a cut off score of 7 and above. We summarised data using descriptive statistics and used logistic regression to explore the risk factors for alcohol use disorder. Results: The prevalence of alcohol use disorder was 39.9.1% (95% CI: 29.35, 41.17) and was more among males as compared to females (p-value = 0.001). Alcohol use disorder was associated with male gender (OR = 0.38), secondary education (OR = 6.16), and living with others (OR = 17.78). Among those who used alcohol, 29.2% (26) were hazardous drinkers, 56.2% (50) were harmful drinkers, and 33.7% (30) were alcohol dependent based on AUDIT item analysis. Conclusion: Gender differences, level of education, and family structure are issues that must be considered in adopting interventions aimed at reducing the burden of alcohol use disorder among adolescents and preventing further spread into adulthood
Keywords: Cross-Sectional Study; Prevalence; Alcohol Consumption; Alcohol Use Disorder; Adolescents